(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Postoperative nausea and vomiting (PONV) continues to be a prevalent and disturbing complication after laparoscopic surgery, resulting in patient discomfort, delayed recovery, and extended hospital stays. The prevalence of PONV is notably elevated following laparoscopic surgeries, attributed to pneumoperitoneum and the administration of anesthetic drugs. Ondansetron and dexamethasone are often utilized antiemetics; nonetheless, comparative data are still few. Aims: To compare the effectiveness of ondansetron and dexamethasone in the prevention of postoperative nausea and vomiting in patients undergoing laparoscopic surgery. Materials and Methods: This prospective observational study was conducted over a period of 12 months in a tertiary care hospital. A total of 90 patients aged 18–65 years, belonging to American Society of Anesthesiologists (ASA) physical status I and II, scheduled for elective laparoscopic surgeries were included. Patients were allocated into two groups based on the antiemetic administered as part of routine anesthetic care. Group O (n = 45) received intravenous ondansetron 4 mg, while Group D (n = 45) received intravenous dexamethasone 8 mg at induction of anesthesia. Standard anesthetic techniques were followed for all patients. Postoperative nausea and vomiting were assessed at 0–6 hours, 6–12 hours, and 12–24 hours using a standardized scoring system. The need for rescue antiemetics and incidence of adverse effects were recorded. Data were analyzed using appropriate statistical tests, with p < 0.05 considered statistically significant. Results: The incidence of PONV within 24 hours postoperatively was reduced in the ondansetron group relative to the dexamethasone group, however the difference was not statistically significant across all time intervals. Early postoperative nausea (0–6 hours) occurred less frequently in patients administered ondansetron. The necessity for rescue antiemetic medication was slightly elevated in the dexamethasone cohort. Both medications were well tolerated, with no major side effects observed in either group. Conclusion: Both ondansetron and dexamethasone effectively diminished the occurrence of postoperative nausea and vomiting after laparoscopic surgery. Ondansetron shown superior management of early postoperative symptoms, although dexamethasone had similar overall effectiveness. Either medication may be utilized well for PONV prophylaxis, contingent upon the patient’s profile and clinical preference.